Combining ability and heterosis analysis for grain yield and its components in wheat - Raj, Preeti; Kandalkar, Vasant S (Journal of Cereal Research, 2013)
Parents and 40 F1s were grown in a randomized block design with two replications. Both general combing ability (GCA) and specific combing ability (SCA) variances were significant for grain yield and all yield component characters, except GCA variances for number of productive tillers per plant, main spike weight, first inter nodelength and grain weight per spike and SCA variances for stem girth, thereby, indicating that grain yield and most of traits were under the control of both additive as well as non-additive inheritance. The combining ability effects revealed that parents HD2964, DDW32, DDW11 and HS493 identified as good general combiners for grainyield and for most of the characters including harvest index. The crosses, DBW39 X HPW285, SONALIKA X RAJ4119, MP4010 X HS493 and MP4010 X HD2964 were good specific combiner for grain yield and either two or more components traits. Most of the good specific combinations for various traits involved parents with highX low or low X low or low X high GCA effects. Heterosis over mid parents and better parent were significant in favorable direction in crosses viz., DBW39 X HD2964, SONALIKA X RAJ4119, SONALIKA X DDW11, DBW17 X RAJ4119, for grain yield and its components.